Report of a case of bilateral Wilms tumor. Management with minimal therapy (Colombia Medica, 1988)
A 3-year-old boy with a bilateral Wilms tumor received a very short course of chemotherapy and radiotherapy. The masses disappeared; there is an apparent cure over three years after diagnosis.